Language Development, Literacy Skills, and Predictive Connections to Reading in Finnish Children With and Without Familial Risk for Dyslexia - Torppa, Minna; Lyytinen, Paula; Erskine, Jane; Eklund, Kenneth; Lyytinen, Heikki (Journal of learning disabilities, 2010)
Discriminative language markers and predictive links between early language and literacy skills were investigated retrospectively in the Jyväskylä Longitudinal Study of Dyslexia in which children at familial risk for dyslexia have been followed from birth. Three groups were formed on the basis of 198 children’s reading and spelling status. One group of children with reading disability (RD; n = 46) and two groups of typical readers from nondyslexic control (TRC; n = 84) and dyslexic families (TRD; n = 68) were examined from age 1.5 years to school age. The RD group was outperformed by typical readers on numerous language and literacy measures (expressive and receptive language, morphology, phonological sensitivity, RAN, and letter knowledge) from 2 years of age onward. The strongest predictive links emerged from receptive and expressive language to reading via measures of letter naming, rapid naming, morphology, and phonological awareness.